2022
DOI: 10.1002/jeq2.20347
|View full text |Cite
|
Sign up to set email alerts
|

In situ stabilization of arsenic and lead in contaminated soil using iron‐rich water treatment residuals

Abstract: Arsenic (As) and lead (Pb) are common soil contaminants, environmentally hazardous, and threats to public health. Addition of soluble phosphate is known to be effective for in situ remediation of Pb-contaminated soils, but phosphate additions displace As from the soil particles and increase As concentration in soil solution. This study examined the dual use of iron (Fe) and phosphorus (P) amendments to soil that was highly contaminated with As and Pb. The test soil originated from a former smelter site in Utah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Bioaccessibility of As associated with Fe ferrihydrite depends on the bond type between iron oxide and As. The sorbed As species have relatively higher bioaccessibility compared to co‐precipitated As with ferrihydrite (Jeong et al., 2017; Kim et al., 2014; Meunier et al., 2010; Rathnayake & Schwab, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Bioaccessibility of As associated with Fe ferrihydrite depends on the bond type between iron oxide and As. The sorbed As species have relatively higher bioaccessibility compared to co‐precipitated As with ferrihydrite (Jeong et al., 2017; Kim et al., 2014; Meunier et al., 2010; Rathnayake & Schwab, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, using the SBRC gastric phase, Silvetti et al [61] showed that treatment of two soils (2428 and 860 mg As kg -1 ) impacted by mining and chromated copper arsenate with an Al-WTRs (13.9% Al) marginally reduced As IVBA (TERs of 0.80-0.81). In contrast, although Rathnayake and Schwab [58] showed significant reductions in As IVBA (USEPA Method 1340) when Fe-WTRs containing 12% Fe were applied to a smelter-impacted soil (7520 mg As kg -1 and 66,400 mg Pb kg -1 ) at Fe:As molar ratios of 2:1, 5:1, and 10:1 (TERs of 0.27, 0.06, and 0.04), a significant reduction in simultaneous Pb and As IVBA was only observed at the highest application rate (TER of 0.79). The ineffectiveness of Fe-WTRs in immobilizing Pb compared to As may be due to the fact that Pb adsorbed by Fe oxides is readily solubilized in gastric solution.…”
Section: Immobilization Efficacy Assessed Using Ivbamentioning
confidence: 94%
“…High Pb TERs have been observed following the use of Al/ Fe-rich WTR amendments, with Pb TERs ranging from 0.93 to 0.99 in Silvetti et al [61], 0.93 to 0.94 in Mele et al [60], and 0.79 to 0.96 in Rathnayake and Schwab [58]. However, Rathnayake and Schwab [58••] reported a TER of 0.26 when using Fe-rich WTRs (Fe:Pb = 10:1) and phosphate (P:Pb = 5:1) simultaneously (using USEPA Method 1340) compared to Fe-rich WTRs alone (TER of 0.96), phosphate alone (TER of 0.50), or sequential application of phosphate followed by Fe-rich WTRs (TER of 0.50).…”
Section: Immobilization Efficacy Assessed Using Ivbamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the effective restoration of As-polluted soils requires sound knowledge of As interaction with soil components. Several researchers have examined the potential of WTRs in restoring As-polluted soils (Nielsen et al, 2011 ; Rathnayake & Schwab, 2022 ; Sarkar et al, 2007a , 2007b ). They found that utilization of Fe WTRs at a rate of 3% successfully stabilized heavily polluted soils with heavy metals including arsenic (Garau et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%